Integration of Saparan Bekakak Tradition to Strengthen the Character Profile of Pancasila Students in History Learning - Agung Bahroni; Risky Setiawan; Vionita Vara Fitrianti (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the character values embedded in the local wisdom of Saparan Bekakak and examines their relevance in strengthening the Pancasila Student Profile within the context of history learning. The integration of cultural heritage in education supports the development of students who are both knowledgeable and rooted in national values. A qualitative research design was employed using a literature study and interviews with cultural practitioners of Saparan Bekakak. A content analysis approach was used to interpret primary data from interviews and secondary data related to the Pancasila Student Profile and character education. The study found that the Saparan Bekakak tradition contains rich character values, including religious devotion, independence, responsibility, mutual cooperation, tolerance, adherence to social norms, and creative problem-solving. These values align closely with the six dimensions of the Pancasila Student Profile. The integration of Saparan Bekakak's character values into Grade XI (Phase F) history learning in Senior High Schools through the CORE learning model supports the formation of 21st-century learners who possess both academic competence and strong character. This local wisdom offers a culturally relevant resource for developing students in line with the goals of the Merdeka Curriculum, emphasizing the importance of contextual and value-based education.